Help please, this is using imaginary numbers just so you know...
Follow Math Help Forum on Facebook and Google+
Hello, Originally Posted by iphysics Help please, this is using imaginary numbers just so you know... Let The equation is now using the discriminant method : --> are the roots of the polynomial. --> Therefore :
Hello, iphysics! Factor: . Factor: . Factor: .
Hi, z^4-2z^2-3 =z^4-3z^2+z^2-3 =z^2(Z^2-3)+1(z^2-3) =(z^2+1)(z^2-3) to calculate z value z^2+1=0 z^2=-1 and z^2-3=0 z^2=3 z=+ or - sqrt3 z=+ or - i
View Tag Cloud